Analisis Ketahanan Sosial Masyarakat “Nusantara” Dalam Pembangunan Ibukota Negara - Annisa Valentina; Marisa Elsera (Jurnal Sosiologi Andalas, 2023)
The development of New State Capital (IKN),"Nusantara", has been in progress and urgently needs more facilities to support its development like Jakarta, the capital of Indonesia. The development would bring more heterogenity of community after movement which may lead to social conflict. The purpose of this study is mapping the condition of social resillence in the "Nusantara" community and to examine the supporting and inhibiting factors for the development of social resilience. The approach applied in this article was a qualitative literature study, by examining the text from online news. The object of this study was development of IKN and its impact in social resilience. Data were collected through online assessments. After that, data were sorted, categorized, and analyzed. The results of the study show that the social resilience of local people is still weak; great effort is needed to strengthen local people’s resilience too increase ability of them to facie challenges in the IKN.